The Effectiveness of Using Picture Series on Students’ Writing Skill In Recount Text At Sma Kampus Nommensen Pematangsiantar - Eksaulina Simanjuntak; Selviana Napitupulu (CV. Doki Course and Training, 2026)
Writing is one of the most challenging skills for EFL students, particularly in producing recount texts that are well organized and linguistically accurate. Many senior high school students still face difficulties in generating ideas, organizing events chronologically, and using appropriate language features in their writing. However, most previous studies have been conducted in junior high school contexts, while research examining the effectiveness of picture series in senior high school settings remains limited. Therefore, this study aimed to investigate the effectiveness of using picture series on students’ writing skill in recount text at the senior high school level. This study employed a quantitative one-group pretest–posttest design involving 23 tenth-grade students of SMA Kampus Nommensen Pematangsiantar. The data were collected through writing tests administered before and after the treatment and analyzed using descriptive statistics and a paired-sample t-test. The results showed that students’ mean writing score improved significantly from 55.43 in the pre-test to 73.48 in the post-test. Beyond demonstrating effectiveness, the findings suggest that picture series support key cognitive processes in writing, particularly idea generation and chronological organization. This indicates that picture series function not only as instructional media, but also as pedagogical support that helps learners transform visual input into coherent written recount texts in EFL contexts.